E-learning: Count on cell phones - Vanska, Riitta; Roberts, Nicky (Technical Centre for Agricultural and Rural Cooperation, 2011)
A project in South Africa supports mathematics education in schools using the web, social networking and mobile apps to deliver learning material directly to students' cell phones. Teachers can also use the content in their classroom lessons.